Supercritical CO2 Extraction and Microencapsulation of Lycopene-Enriched Oleoresins from Tomato Peels: Evidence on Antiproliferative and Cytocompatibility Activities - Liliana Mihalcea; Oana Crăciunescu; Ionica Gheonea (Dima); Ana-Maria Prelipcean; Elena Enachi; Vasilica Barbu; Gabriela Elena Bahrim; Gabriela Râpeanu; Anca Oancea; Nicoleta Stănciuc (MDPI AG, 2021)
Tomato peels are used as a valuable material to extract lycopene-rich oleoresins by supercritical CO2 extraction. The extraction involves continuous circling of CO2 to the extractor after removing the solute in the separators, S40 and S45, where the solvent power of the CO2 is reduced by reducing pressure down to 20 MPa in S40 and 5 MPa in S45, respectively, leading to two extracts. Lycopene is found to be the major compound, representing 93% and 76% of the total carotenoids in S40 and S45 extracts, respectively. The two extracts are microencapsulated in whey protein concentrate and acacia gum by complex coacervation and freeze-drying, leading to corresponding P40 and P45 powders, with antioxidant activity of 8.57 ± 0.74 and 9.37 ± 0.48 mMol TEAC/g DW in P40 and P45, respectively. Different structural and morphological patterns are observed, with finer microparticles of 1-2 µm in P45. Both powders show dose and time-dependent antiproliferative activity. The half-maximal inhibitory concentration values are 100 µg/mL for P40 and 750 µg/mL for P45 sample, indicating a higher antiproliferative effect of P40 over P45 in HT-29 cell culture. The powders have an extended range of cytocompatibility, up to 1000 µg/mL, in L929 normal cells, stimulating the cell growth. Lycopene retention is tested, and values of 48% and 29% in P40 and P45 are found after 21 days at 25 °C, with the degradation rate in P45 significantly higher, due to the higher content of the surface lycopene, which favored its degradation.